Reprogramming of a human induced pluripotent stem cell line from one 48-year-old healthy male donor - Ruiyun Guo (Stem Cell Research, 2021)
In this study, skin biopsy was collected from a healthy 48-year old male donor with informed consent, and the fibroblasts were isolated from the dermal explant cultures. Here, a human induced pluripotent stem cell (iPSC) line was derived from the fibroblasts using the reprogramming four Yamanaka factors (Oct3/4, Sox2, Klf4, c-Myc). The generated iPSCs were integration-free, displayed the normal karyotype, expressed pluripotency markers and demonstrated trilineage differentiation potential in vitro. This iPSC model will be useful for investigating physiological processes, drug validation as well as a control in pathological mechanistic studies.